2000
DOI: 10.1074/jbc.m002740200
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor-α Binding and Ubiquitylation by the von Hippel-Lindau Tumor Suppressor Protein

Abstract: The von Hippel-Lindau tumor suppressor protein (pVHL) has emerged as a key factor in cellular responses to oxygen availability, being required for the oxygen-dependent proteolysis of ␣ subunits of hypoxia inducible factor-1 (HIF). Mutations in VHL cause a hereditary cancer syndrome associated with dysregulated angiogenesis, and up-regulation of hypoxia inducible genes. Here we investigate the mechanisms underlying these processes and show that extracts from VHL-deficient renal carcinoma cells have a defect in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
622
1
8

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 949 publications
(640 citation statements)
references
References 34 publications
6
622
1
8
Order By: Relevance
“…A difference in location and area of positive staining (Wykoff et al, 2000;Olive et al, 2001 and also the present study) supports this explanation. von Hippel-Lindau mutations, which result in an upregulation of HIF-1a (Cockman et al, 2000) and downstream components like CA IX (Ashida et al, 2002), and the relationship between CA IX expression and acidic pH found in tumours (Stubbs et al, 2000) could potentially contribute to the published differences.…”
Section: Discussionmentioning
confidence: 99%
“…A difference in location and area of positive staining (Wykoff et al, 2000;Olive et al, 2001 and also the present study) supports this explanation. von Hippel-Lindau mutations, which result in an upregulation of HIF-1a (Cockman et al, 2000) and downstream components like CA IX (Ashida et al, 2002), and the relationship between CA IX expression and acidic pH found in tumours (Stubbs et al, 2000) could potentially contribute to the published differences.…”
Section: Discussionmentioning
confidence: 99%
“…Hs.HIF-2a (Cockman et al, 2000) to introduce novel restriction sites without changing the encoded protein using primers listed in Supplementary Table 1. After confirmation by restriction digestion and DNA sequencing, the sites introduced were used to allow domain exchange by standard recombinant techniques.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…The VHL gene product pVHL is a critical component of a multiprotein ubiquitin ligase complex that targets the regulatory HIF-a subunits of hypoxia-inducible factor 1 (HIF-1) for oxygen-dependent proteolysis (Iwai et al, 1999;Maxwell et al, 1999;Cockman et al, 2000;Ivan et al, 2001). HIF-1 is expressed in response to hypoxia in most cell types and activates the transcription of genes involved in a variety of physiological and cellular processes including vascular endothelial growth factor (VEGF), glucose transport (glucose transporters), glycolysis (glycolytic enzymes), and cell survival (insulin-like growth factor 2) (Semenza, 1999).…”
mentioning
confidence: 99%